1981
DOI: 10.1177/003693308102600409
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Immigrant Children in the Centre of Glasgow

Abstract: One hundred and ninety six Asian, 89 African, 96 Chinese and 98 Scottish children from 173 families were studied to assess growth in relation to country of birth, time of parental residence in Scotland, child order in family, social class, living conditions and dietary factors. The growth measurements (standardised height, weight and bone age) differed between ethnic groups. The Africans were the tallest and Scottish the shortest. In all immigrant groups, children born in Scotland were on average, taller and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The developing dentition is known to be less sensitive to physiological insults (nutrition, endocrine) than the skeleton [20–24]. Growth of infants and young children from ethnic groups of the Indian subcontinent living in other parts of the UK is similar to national reference data [25–28]. In addition, growth of older local Bangladeshi children is also similar to the UK growth standards (personal communication, G. Snodgrass).…”
Section: Discussionmentioning
confidence: 86%
“…The developing dentition is known to be less sensitive to physiological insults (nutrition, endocrine) than the skeleton [20–24]. Growth of infants and young children from ethnic groups of the Indian subcontinent living in other parts of the UK is similar to national reference data [25–28]. In addition, growth of older local Bangladeshi children is also similar to the UK growth standards (personal communication, G. Snodgrass).…”
Section: Discussionmentioning
confidence: 86%
“…We must infer that the insults suffered by the children in these studies may have been qualitatively different from those suffered by Datoga children and other stunted populations in which a failure to catch up was reported (Golden, 1996). Other studies have demonstrated catch-up growth among stunted children moved to conditions of better nutrition and lower disease exposure Adrianzen, 1971, 1972;Winick et al, 1975;Lien et al, 1977;Goel et al, 1981;King and Taitz, 1985;Mjones, 1987;Schumacher et al, 1987;Steckel, 1987), supplemented with food (Super et al, 1990), or treated for disease (Tanner, 1981). Secular trends of increased height for age and earlier maturation have been reported for populations where improved conditions persist across generations (Eveleth and Tanner, 1990).…”
Section: Lack Of Catch-up Growth and Adolescent Growth ''Faltering''mentioning
confidence: 98%
“…A total of 19 articles discuss physical and developmental health [61,95,119,[156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171] and shed light on AMC's growth and development. For example, AMC in Israel, the United States, and France are more likely to fail tests assessing fine-motor skill, linguistic, and socio-emotional domains [156], and to have poor growth [61] and a low BMI [61].…”
Section: Physical and Developmental Healthmentioning
confidence: 99%